Epistemological Approach To Time Dilation Idea In The Theory Of Relativity - ملحم, عدنان; الحلاق, إبراهيم علي (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research sheds light on the concept of TIME in physics from epistemological Point, trying to show logical paradox in its usage . The concept of TIME is Intellectual And unmaterial concept, and human invention, and we tend to consider it metaphysical ,then it is used in physics as one of material components for physical processes . So We intended to clear this paradox and clarifying that shoving the concept of TIME in This place due to human framing the scientific assumption in appropriate way to his Understanding .